The Influence of Competency on Performance in Regional Equipment of North Sumatra Province - Prestiany, Neny; Isa Indrawan, Muhammad (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
The purpose of this research is to determine and analyze the influence of competency on employee performance in North Sumatra Human Resources Development Agency employees. This research was carried out at the North Sumatra Human Resources Development Agency. The type of research is associative quantitative. The sample in this study was 107 employees of the North Sumatra Human Resources Development Agency. The sampling technique in this research uses saturated samples so that the entire population will be a sample of 107 people. The research results show that Competency has a significant influence on Employee Performance as shown by the T-Statistic value of 3.826 > 1.659 and the P Value of 0.000 < 0.05. This shows that improvements in competency will be able to contribute to improving employee performance at the North Sumatra Human Resources Development Agency.